KREATIVITAS GURU PAI DALAM MENGEMBANGKAN MEDIA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Atina Rahmatia; Qiso, Ahmad; Muhammad Wahyudi (An Najah (Jurnal Pendidikan Islam dan Sosial Keagamaan), 2025)
Teachers' creativity in developing learning media plays a crucial role in providing engaging, relevant, and effective learning experiences that benefit the learning process. However, there is still a lack of knowledge among Islamic Education (PAI) teachers regarding learning media, such as their limited mastery of software. The purpose of this research is to investigate and describe how teachers’ creativity is applied in developing learning media at SDN 7 Pemulutan Barat, as well as to identify and describe the supporting and inhibiting factors in the development of learning media at SDN 7 Pemulutan Barat. This study employs a qualitative descriptive approach (field research). The research method uses a qualitative approach with the theme "Creativity of PAI Teachers in Developing Learning Media at SDN 7 Pemulutan Barat" as the research object, involving PAI teachers, teacher leaders (guru penggerak), and students as respondents. Data collection techniques include observation, interviews, and documentation, while data analysis techniques involve data reduction, data presentation, and data verification. The research findings are as follows: (1) It can be concluded that in PAI (Islamic Education) learning at SDN 7 Pemulutan Barat, in terms of creativity, PAI teachers develop learning media using methods that align with the material to be taught, taking into account the content, objectives, methods, and characteristics of the students in the classroom. This approach ensures that the use of learning media remains consistent with the intended goals and is reviewed beforehand, making it easier for students to understand the material with the aid of learning media. (2) The supporting factors include the school environment and fellow teachers. (3) The inhibiting factors are the limited availability of projectors, laptops, internet networks, and frequent power outages.